Adjunctive antidepressant use in schizophrenia in China: A national survey (2002–2012). (January 2017) - Li, Qian; Su, Yun‐Ai; Xiang, Yu‐Tao; Shu, Liang; Yu, Xin; Ungvari, Gabor S.; Ng, Chee H.; Chiu, Helen F.K.; Ning, Yu‐Ping; Wang, Gao‐Hua; Zhang, Ke‐Rang; Li, Tao; et al.
Abstract: Objective: This study examined the pattern of adjunctive antidepressant use in schizophrenia patients and its demographic and clinical correlates in a nationwide survey in China. Methods: Fourteen thousand and thirteen patients in 45 Chinese psychiatric hospitals or centers were interviewed (4, 486 in 2002, 5, 288 in 2006, and 4, 239 in 2012). Patients' sociodemographic and clinical characteristics were recorded using a standardized protocol and data collection procedure. Chi‐square test, independent‐samples t test, Mann–Whitney U test, and multiple logistic regression analysis were used in data analyses. Results: Antidepressant use was found in 5.2% of the study population with 4.6% in 2002, 4.3% in 2006, and 6.9% in 2012, respectively. A significant increase in use from 2006 to 2012 was found ( p < .001). Multiple logistic regression analyses in the whole population revealed that patients receiving adjunctive antidepressants were more likely to be outpatients in tertiary referral centers (level‐III hospitals) and who had an earlier age of onset, less severe global illness, but more depressive symptoms. They were less likely to receive first‐generation antipsychotics but more likely to receive benzodiazepines (R 2 = 0.255, p < .001). Conclusions: Despite an increasing trend, the frequency of antidepressant use in schizophrenia in China was considerably lower than in Western countries. The benefits and risks associated with concomitant use of antidepressants in schizophrenia need to be studied further.